Physicomechanical properties of composite plaster of Paris from locally grown sisal fiber and gypsum - Abdulganiyu Sanusi; Akeem Gbenga Amuda; Adekunle Adeleke; Abdulhameed Danjuma Mambo; Mahamat Abakar Mahamat; Peter Ikubanni (Discover Civil Engineering)
Abstract The components of POP ceiling boards (POP-CB) in Nigeria consist of gypsum cement and sisal fiber (SF), which are typically imported, resulting in higher construction costs for roof finishes. This study sourced fiber locally from a fiber plant, treating some specimens with NaOH (LSF-2) and others with NaCl (LSF-3), while some remained untreated (LSF-1). In total, four types of specimens were used in the experiment, including foreign sisal fiber (FSF). All fiber specimens were tested for tensile strength, density, flexural strength, drop to fracture (DF), and water absorption according to ASTM and British standards to evaluate the physicomechanical properties of the produced POP-CB. Additionally, microstructural and elemental characterizations of the products were conducted. The tensile strength of LSF-3 reached 257 MPa, which is 95% of the tensile strength of FSF, while the other specimens exhibited lower values. The recorded densities of the POP-CB samples (928–973 kg/m3) and flexural strengths (0–0.158 MPa) were within ASTM standards recommendation for ceiling board to support roof load. Overall, the experimental study indicated that the POP-CB produced with LSF treated with 3wt% NaCl solution performed best after FSF and can serve as a viable replacement for FSF in the production of POP-CB in Nigeria.